PENDAPATAN DAN PENGELUARAN MASYARAKAT PESISIR DANAU LINDU (STUDI EMPIRIS DI DESA LANGKO KECAMATAN LINDU KABUPATEN SIGI) - Rantjanabi, Sulprianti (Katalogis, 2017)
Primary Secondary and tertiary households of Lindu and West Lindu sub district in the Sigi district. There were forty-two households involved in this study as respondents.The data was collected through observation, guestionnaires, interviews, and dokumentation. The data was collected through collecting primaryÂ  data and secondary data. Then, it was classified by the components in accordance with the reguired data linkage. Descriptive analysis techniques with a qualitative apporach is employed in this study. The data was analysed by using tables with depicts frequency. This study found that most of household communities in the western part of Sigi distric are low-income households so that the welfare level is also low. Engel theory states that the higher levels of household income. The percentage of food consumption expenditure is lower. Based on this classical theory, the household can be said to be more prosperous if the percentage of expenditure on food consumption. Based on this classical theory, the household can be said to be more prosperous if their percentage of food expenditure is lower compare to non-food expenditure. This means that the proportion of food expenditure allocations will be smaller while household income increase because most of the revenues are allocated to non-food. The lower level of household welfare or income, the higher allocation level on food than non-food needs and in reverse.